2018
DOI: 10.1177/0300060517721071
|View full text |Cite
|
Sign up to set email alerts
|

Role of quantitative analysis of T2 relaxation time in differentiating benign from malignant breast lesions

Abstract: ObjectiveTo investigate the role of quantitative analysis of T2 relaxation time in the magnetic resonance imaging (MRI) diagnosis of breast cancer.MethodsThe study enrolled patients with clinical breast masses who were examined using MRI at eight different echo times. The differences in T2 relaxation time of benign and malignant breast lesions were analysed.ResultsA total of 67 patients (67 breast lesions: 46 malignant, 21 benign) were examined. The mean ± SD T2 relaxation time was significantly lower in the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 22 publications
(51 reference statements)
6
55
0
Order By: Relevance
“…Literature suggests that change in relaxation times could be useful in predicting early response to chemotherapy and may reflect changes in tumor tissue properties before a measurable decrease in tumor size (10,11,21,22). MR fingerprinting-relaxometry may potentially also be useful in further differentiation of benign and malignant lesions that show similar enhancement patterns with conventional imaging methods (23). Although all the T1 and T2 measurements in our current study were performed before contrast administration, MR fingerprinting can also be performed after contrast administration and the difference in pre-and postcontrast measurements could provide further information about breast lesions than those from precontrast measurements alone.…”
Section: Discussionmentioning
confidence: 92%
“…Literature suggests that change in relaxation times could be useful in predicting early response to chemotherapy and may reflect changes in tumor tissue properties before a measurable decrease in tumor size (10,11,21,22). MR fingerprinting-relaxometry may potentially also be useful in further differentiation of benign and malignant lesions that show similar enhancement patterns with conventional imaging methods (23). Although all the T1 and T2 measurements in our current study were performed before contrast administration, MR fingerprinting can also be performed after contrast administration and the difference in pre-and postcontrast measurements could provide further information about breast lesions than those from precontrast measurements alone.…”
Section: Discussionmentioning
confidence: 92%
“…As the basic intrinsic properties of MRI physics, quantitative T1 and T2 mapping have attracted increasing attention in recent years due to their potential utility [14,15]. Moreover, previous studies have demonstrated that quantitative MRI has the potential to diagnose breast cancer [11,[16][17][18]. However, the long acquisition time of conventional technologies has limited their clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of T 1 and T 2 relaxation times can provide additional information about normal and diseased breast tissue . Previous studies on breast relaxometry have observed significant differences in T 1 and T 2 relaxation times between normal fibroglandular breast tissue and benign and malignant breast tumors . Changes in T 2 relaxation time has also been used to characterize response to chemotherapy in breast cancers .…”
mentioning
confidence: 99%
“…4,5 Previous studies on breast relaxometry have observed significant differences in T 1 and T 2 relaxation times between normal fibroglandular breast tissue and benign and malignant breast tumors. 5,6 Changes in T 2 relaxation time has also been used to characterize response to chemotherapy in breast cancers. [7][8][9] However, the T 1 and T 2 values reported for normal breast tissue show a wide variation due to the differences in mapping techniques and field strengths.…”
mentioning
confidence: 99%